Dental care utilization during pregnancy by Medicaid dental coverage in 26 states: Pregnancy risk assessment monitoring system 2014–2015. (13th December 2021) - Lee, Hyewon; Marsteller, Jill A.; Wenzel, Jennifer
Abstract: Objective: To examine the association between Medicaid dental coverage for adult pregnant women with dental care utilization during pregnancy. Methods: Pregnancy risk assessment monitoring system (PRAMS) data (2014–2015) and the Medicaid‐SCHIP state dental association (MSDA) national profiles (2014–2015) were used in this study. The study sample included 16, 612 Medicaid‐enrolled women, for a weighted number of 965, 046 women from 26 states and New York City. State Medicaid dental coverage was categorized into (1) no coverage for the dental cleaning, (2) coverage for dental cleaning and fillings, (3) extended dental coverage. The adjusted prevalence ratios (aPR) for dental visits for cleaning during pregnancy were examined by Medicaid dental coverage level. Results: Medicaid‐enrolled women in states with no dental coverage were less likely to visit dentists for cleaning during pregnancy (26.7%) compared with women in states with either limited dental coverage (36.6%) or extended dental coverage (44.9%). Compared with women in state without dental coverage, Medicaid‐enrolled women in states with extended dental coverage (aPR = 1.20, 95% CI [1.16–1.23]) and women in states with limited coverage (aPR = 1.10, 95% CI [1.06–1.14]) were more likely to visit dentists for cleaning during pregnancy when adjusted for other sociodemographic variables and adequacy of prenatal care. A similar pattern of association was observed for a dental visit to address dental problems during pregnancy. Conclusions: This study highlights the importance of Medicaid dental coverage for adult pregnant women related to dental service utilization during pregnancy.